Using mathematical induction, prove that for every positive integer n,
1 · 2 + 2 · 3 + · · · + n(n + 1) = (n(n + 1)(n + 2)) / 3
Base step
for n=1: "1*2=\\frac{1*2*3}{3}=2." The statement holds.
Inductive step
Assume that for n=k: "1*2+2*3+...+k(k+1)=\\frac{k(k+1)(k+2)}{3}"
Then, for n=k+1: "1*2+2*3+...+k(k+1)+(k+1)(k+2)=\\frac{k(k+1)(k+2)}{3}+(k+1)(k+2)="
"=(k+1)(k+2)(\\frac{k}{3}+1)=\\frac{(k+1)(k+2)(k+3)}{3}"
That is, the statement for n=k+1 also holds true.
Since both the base step and the inductive step have been proved as true, by mathematical induction the statement holds for every natural number n.
Comments
Leave a comment